Risk Aversion, Liquidity, and Endogenous Short Horizons - Holden, Craig W.; Subrahmanyam, Avanidhar (Review of Financial Studies, 1996)
We analyze a competitive model in which different information signals get reflected in value at different points in time. If investors are sufficiently risk averse, we obtain an equilibrium in which all investors focus exclusively on the short term. In addition, we show that increasing the variance of informationless trading increases market depth but causes a greater proportion of investors to focus on the short-term signal, which decreases the informativeness of prices about the long run. Finally, we also explore parameter spaces under which long-term informed agents wish to voluntarily disclose their information.